2019
DOI: 10.1292/jvms.18-0644
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pubertal exposure to high temperature impairs ovarian and adrenal gland function in female rats

Abstract: The influence of different levels of heat exposure on the functions of ovarian and adrenal gland were investigated in pre-puberty female rats. Three-week old female rats were treated with control (26°C) or three higher temperatures (38, 40 and 42°C) for 2hr/day. After 9 days of treatment, blood samples were collected for measurement of luteinizing hormone (LH), follicle stimulating hormone (FSH), estradiol-17β, corticosterone, cholesterol and triglyceride. Adrenal glands, ovaries and liver were collected for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Therefore, it is suggested that L-arginine might reduce the disorder of the estrous cycle in rats by regulating glucose and lipid metabolism and amino acid synthesis during HE. Studies have shown that high temperature inhibits ovarian function and reduces the follicular growth rate ( Zheng et al, 2019 ). As a potential endocrine disruptor with estrogenic activity, the phthalic acid mono-2-ethylhexyl ester may inhibit follicular growth through the oxidative stress pathway ( Zhang et al, 2018 ) and by reducing estradiol production ( Wang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is suggested that L-arginine might reduce the disorder of the estrous cycle in rats by regulating glucose and lipid metabolism and amino acid synthesis during HE. Studies have shown that high temperature inhibits ovarian function and reduces the follicular growth rate ( Zheng et al, 2019 ). As a potential endocrine disruptor with estrogenic activity, the phthalic acid mono-2-ethylhexyl ester may inhibit follicular growth through the oxidative stress pathway ( Zhang et al, 2018 ) and by reducing estradiol production ( Wang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental animals were fed in cages for 2 days, followed by vaginal cytological smears at the same time each morning and evening. A total of 44 rats were randomly divided into two groups (with regular estrous cycles): (1) control group (C group)—the animals were fed under standard temperature and humidity conditions; and (2) HE group (H group)—each model animal was exposed to heat (38°C ± 0.5°C; relative humidity 55% ± 5%) for 2 h/day (9:00–11:00) in a small-animal heat chamber ( Zheng et al, 2019 ; An et al, 2020 ). The experiment lasted for at least 90 days with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…It is not suitable for the further study of the human menstrual cycle. There are few studies on heat stress in female rats, and the modeling conditions are different, and the conclusions are inconsistent [1,4,13,14]. Herein, we proposed a 90-day heat stress model to redefine the temperature, duration, and frequency of heat exposure and established a stable and effective rat estrus cycle disorder model on the premise of no heatstroke.…”
Section: Discussionmentioning
confidence: 99%
“…The degeneration of ovarian tissue and reduction in folliculogenesis and oogenesis were also observed as responses to thermal injury in females ( Zheng et al, 2019 ). In prepubertal female Wistar rats, Zheng et al (2019) observed the ovarian function of these animals in the face of thermal stress at different temperatures (38, 40, and 42 °C for 2 h/ day). The plasma levels of LH and triglycerides and the expression of LH receptors FSH and estradiol-17β in the ovaries were significantly lower at higher temperatures (especially at 42 °C) than in the control (26 °C).…”
Section: Temperaturementioning
confidence: 99%